Estimate of an error of the averaging method on a semiaxis for a multifrequency resonance system - Petryshyn, R. I.; Pokhyla, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
In this paper, we justify the averaging method for a multifrequency resonance system on a semiaxis under the assumption that the normal fundamental matrix of a variational system of averaged equations for slow variables exponentially tends to zero. We also study the quantitative dependence of the estimates on the magnitude of a small parameter.